The art of Jane Orleman: childhood trauma and the discourse of sexual violence - Kwon, Hyunji (Journal of Gender Studies, 2023)
Jane Orleman (American, born 1942) is an artist and a survivor of child sexual abuse. Through paintings she created during therapy, Orleman rejects the gendered and patriarchal binaries between therapeutic art and professional art, which pit the private, feminine, and intuitive against the public, masculine, and intellectual. By analysing selected artworks from Orleman that embody her child self, young woman self, and alternative self, I propose that Orleman reflects on and challenges the pathology of sexual trauma along with the discourse of sexual violence as a political statement. Therefore, I argue that her art deserves to be part of a larger, counternarrative, anti-rape and anti-incest cycle in contemporary American art.
Keywords: Sexual violence; art; survivor; therapy; trauma